2022
DOI: 10.1186/s13073-022-01071-5
|View full text |Cite|
|
Sign up to set email alerts
|

Acetyl-CoA metabolism drives epigenome change and contributes to carcinogenesis risk in fatty liver disease

Abstract: Background The incidence of non-alcoholic fatty liver disease (NAFLD)-associated hepatocellular carcinoma (HCC) is increasing worldwide, but the steps in precancerous hepatocytes which lead to HCC driver mutations are not well understood. Here we provide evidence that metabolically driven histone hyperacetylation in steatotic hepatocytes can increase DNA damage to initiate carcinogenesis. Methods Global epigenetic state was assessed in liver sample… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…Cluster-1, the gene-set was found to be expressed in Liver, and found to be related with HDL, Amyloid protein and hemolytic anemia. It was also found to be linked with metabolism of Folate & Vita-12 [8, 9, 10] (Figure 6).…”
Section: Results and Discussuionmentioning
confidence: 99%
“…Cluster-1, the gene-set was found to be expressed in Liver, and found to be related with HDL, Amyloid protein and hemolytic anemia. It was also found to be linked with metabolism of Folate & Vita-12 [8, 9, 10] (Figure 6).…”
Section: Results and Discussuionmentioning
confidence: 99%
“…In steatotic hepatocytes, hyperacetylation of genome-wide histones could initiate carcinogenesis by damaging DNA. 101 Recent studies have found that the concurrent activation of acetylated and trimethylated H3K9 in mice can lead to NASH-related HCC, and deacetylation of H4K16 promotes cancer progress by silencing genes associated with cell death. 102,103 In addition to these findings, histone modifications caused by the interactions between a HFD and intestinal microbiome are significant during gastrointestinal tumor development.…”
Section: The Impact Of Histone Modifications On Cancer-related Gene E...mentioning
confidence: 99%
“…Chromatin becomes slack due to histone acetylation, thereby increasing DNA accessibility and promoting transcriptional activity. In steatotic hepatocytes, hyperacetylation of genome‐wide histones could initiate carcinogenesis by damaging DNA 101 . Recent studies have found that the concurrent activation of acetylated and trimethylated H3K9 in mice can lead to NASH‐related HCC, and deacetylation of H4K16 promotes cancer progress by silencing genes associated with cell death 102,103 .…”
Section: Histone Modification In Obesity‐associated Diseasesmentioning
confidence: 99%
“…The exact mechanisms by which fructose modifies urine composition are still not completely understood and a specific epigenetic mechanism exerted by fructose in nephrolithiasis or risk factors for kidney stone formation have not been described. However, from available data, we know that fructose acts via epigenetic mechanisms (ncRNA and DNA methylation) in other conditions [ 57 , 58 , 59 ], such as nonalcoholic fatty liver disease (NAFLD) [ 60 , 61 , 62 ]. Therefore, we can speculate that fructose might act via epigenetic mechanisms to regulate the expression of genes that encode crucial transporters of anti- and prolithogenic urinary molecules.…”
Section: Food Compoundsmentioning
confidence: 99%